Mesenchymal Stem Cells - Basics and Clinical Application I - Weyand, Birgit.; Weyand, Birgit.; Dominici, Massimo.; Dominici, Massimo.; Hass, Ralf.; Hass, Ralf.; Jacobs, Roland.; Jacobs, Roland.; Kasper, Cornelia.; Kasper, Cornelia. (Advances in Biochemical Engineering/Biotechnology,, 2013)
A. Harichandan K. Sivasubramaniyan H.-J. Bühring Prospective Isolation and Characterization of Human Bone Marrow-Derived MSCs Christina Benda Ting Zhou Xianming Wang Weihua Tian Johannes Grillari Hung-Fat Tse Regina Grillari-Voglauer Duanqing Pei Miguel A. Esteban Urine as a Source of Stem Cells Sven Kinzebach Karen Bieback Expansion of Mesenchymal Stem/Stromal Cells under Xenogenic-Free Culture Conditions Danielle Minteer Kacey G Marra J Peter Rubin Adipose-Derived Mesenchymal Stem Cells: Biology and Potential Applications Antonina Lavrentieva Tim Hatlapatka Anne Neumann Birgit Weyand Cornelia Kasper Potential for Osteogenic and Chondrogenic Differentiation of MSC Letizia Ferroni Chiara Gardin Ilaria Tocco Roberta Epis Alessandro Casadei Vincenzo Vindigni Giuseppe Mucci Barbara Zavan Potential for Neural Differentiation of Mesenchymal Stem Cells Thomas Dittmar Frank Entschladen Migratory Properties of Mesenchymal Stem Cells Stefania Bruno Federica Collino, Ciro Tetta Giovanni Camussi Dissecting Paracrine Effectors for Mesenchymal Stem Cells Yin Xiao Jiezhong Chen Proteomics Approaches in the Identification of Molecular Signatures of Mesenchymal Stem Cells Richard Schäfer Does the Adult Stroma Contain Stem Cells?